The effect of (TRX) exercises in improving muscle strength in terms of ranges of motion of the spine for high jumpers with low back pain, ages (25-35 years) (Texas Journal of Multidisciplinary Studies, 2023)
The rehabilitative natural curative methods are among the important and safe means that the world's attention has begun to turn to because it secures human life in all its affairs. Therapeutic exercises are an effective and natural method that does not expose the patient to complications on other body functions because it is free of any harmful chemical drugs. Modern techniques have also been widely used in physical therapy, prepared according to scientific foundations, including (TRX) exercises that help relieve pain, especially lower back pain. The sample was between the ages of 25-30 years old, among the high jumpers who had herniated discs for the fourth and fifth Vertebrae. Pre and post tests were conducted for strength from the forward and backward bending position with the force sensor and the flexibility of the spine for forward and backward bending. The researcher concluded the significant differences in the strength and flexibility tests of the spine. In light of the statistically extracted results, TRX exercises should be applied to other injuries to improve strength in terms of the motor ranges of the spine for high jumpers with lower back pain. The researchers also recommend publishing booklets placed in physical therapy centers to benefit from postgraduate research